2020
DOI: 10.3389/fped.2020.591520
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Associated With Urinary Stone Disease in Children and Young Adults Presenting to a Pediatric Emergency Department

Abstract: Background: Acute kidney injury (AKI) due to urinary stone disease (USD) is rare in adults; AKI rates in children with USD may be higher, and emerging data links stones to chronic kidney disease (CKD) development in adults.Methods: This study is a retrospective analysis of USD patients at a single pediatric hospital system's emergency department (ED). Patients were initially identified by USD ICD codes; USD was then confirmed by imaging or physician documentation; patients had to have baseline creatinine (Cr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The present study, renal stone were more common in men (66.7%) than women (33.3%). These result were agreed with Manglaviti et al (9) who found that renal stone more common in male (70%), in contrast to series which was done by Sellaturay and Fry (12) who reported that renal stones were more in males (70%) than in female (30%).…”
Section: Discussionsupporting
confidence: 91%
“…The present study, renal stone were more common in men (66.7%) than women (33.3%). These result were agreed with Manglaviti et al (9) who found that renal stone more common in male (70%), in contrast to series which was done by Sellaturay and Fry (12) who reported that renal stones were more in males (70%) than in female (30%).…”
Section: Discussionsupporting
confidence: 91%